Government expenditure and human capital development in Nigeria: Lessons from the Malaysian experience - Daud, Mustafa (2008)
The significant role and position of human capital in achieving meaningful, purposeful and sustainable economic growth and development in any nation seems to be uncontestable. This is because human capital is a sine qua non for development, particularly for LDCs and emerging economies like Nigeria. Therefore,any country that misplaces the priority of Human Capital Development (HCD) will indeed go nowhere as far as development is concerned. This paper therefore made a historical overview of human capital development in Nigeria vis-à-vis government expenditure in key sectors like education, health etc. that have direct and positive impact on HCD. This overview becomes imperative for policy focus and guide of the government, in view of the fact that the major thrust of the administration is to make Nigeria one of the biggest and leading economies by the year 2020. However, going through historical records, it became clear that factors such as unpatriotic leadership, endemic corruption, misplacement of priority, political instability, inadequate funding of key sectors etc. impacted negatively on HCD. In order to make possible the realisation of “Vision 2020” (which holds enormous development potentials and opportunities for the country), then the Nigerian government needs to adopt some lessons from the Malaysian experience,particularly as it relates to HCD. Some of the lessons identified include: Comprehensive Perspective Plan, appropriate and timely execution of HCD-oriented programmes and projects, adequate budgetary allocations to key sectors that have direct and immediate impact on HCD, timely presentation and passage of the budgetary appropriation bill, special preference for the proliferation of ICT among the workforce,granting fiscal incentives to the private sectors that are HCD inclined and adequate recognition and appropriation of the socio-cultural and religious peculiarities of the federating units for possible optimum development.